Journey of Red Ribbon Express (RRE) through Gujarat - Hemant Shukla1; Hardik Shah (Indian Association of Preventive and Social Medicine, 2010)
Generating mass awareness regarding HIV/AIDS is an important strategy under National AIDS Control Programme-III (NACP-III). It not only reduces the transmission but also aims to remove the stigma and discrimination towards People Leaving with HIV/AIDS (PLHA). This in turn, facilitates the PLHA to come out in open with their status, whereby they join the services of care, supports and treatment and are also empowered/ informed to prevent further transmission.......